NSGA-II Portfolio Optimization: A Comparison of Shariah Stocks (JII70) and Conventional Stocks (LQ45) - Delila Nasywa Ramananda; Dwi Eko Waluyo; Ana Kadarningsih; Suhita Whini Setyahuni (Journal of Management Economics and Financial Accounting, 2026)
This study analyzes and compares the performance of shariah and conventional stock portfolios in the Indonesian capital market using the Non-Dominated Sorting Genetic Algorithm II (NSGA-II) method. The study uses daily closing stock price data from January 3, 2022, to December 30, 2025, which was processed into measures of return and risk as the basis for portfolio construction. Optimization was performed by maximizing expected return and minimizing risk to generate an efficient frontier. Portfolio performance was then evaluated using the Sharpe Ratio, Sortino Ratio, and Omega Ratio. The results show that the shariah stock portfolio outperformed the conventional stock portfolio, as evidenced by a Sharpe Ratio of 0.15 compared to 0.04. Nevertheless, a combination portfolio consisting of shariah stocks and conventional stocks yielded the best overall performance, with a Sharpe Ratio of 0.15, a Sortino Ratio of 0.22, and an Omega Ratio of 1.56. These findings indicate that diversification between shariah and conventional stocks can enhance portfolio efficiency and generate more optimal performance compared to using each group of stocks separately. Thus, the NSGA-II method has proven effective in generating optimal portfolios to support investment decision-making in the Indonesian capital market.